PSYCHOLOGICAL ASPECTS OF STUDYING PATIENTS WITH SKIN AND VENEREAL DISEASES (World Bulletin of Public Health, 2022)
This paper examines the psychological state of venereal patients in relation to their disease, as well as the differences in the manifestation of mental states in women and men of different age categories